ANALISIS FRAMING PEMBERITAAN LARANGAN THRIFTING PADA MEDIA KOMPAS.COM PERIODE TANGGAL 18 - 22 MARET 2023 - Nur Laila, Zulaikha; Suryo S, Herning (Solidaritas, 2025)
This research analyzes the framing of news related to the ban on thrifting in the Kompas.com media for the period 18 - 22 March 2023 using the framing analysis model of Zhongdang Pan and Gerald M. Kosicki, which includes four structural dimensions (syntactic, script, thematic and rhetorical). This research uses a qualitative descriptive approach with documentation data collection and data selection techniques. Data were obtained from articles published during that period. The results of the analysis show that there is a change in the focus of framing in the news. In the first to fourth news, Kompas.com emphasized government policy which prohibits thrifting because it is considered to damage micro, small and medium enterprises (MSMEs). The fifth news item presentsconsumers' responses to the ban, while the sixth news item provides solutions for affected traders. In the seventh news, Kompas.com presents arguments from several fashion specialists regarding the ban on thrifting. Based on the analysis of the structure of the news script presented by Kompas.com which meets the 5W+1H elements, this report focuses more on the government's perspective which supports the ban on thrifting, with an emphasis on Minister of Trade regulation no. 18 of 2021 Article 2 Paragraph 3 which assesses that thrifting can harm MSMEs. Kompas.com presents news in language that is easy to understand, allowing the audience to understand the policy clearly. Keywords: framing, thrifting, Kompas.com